Collection Development of Library Materials at Universitas Pendidikan Nasional - Ni Made Merlina Dwi Heriani; Laylatul Munawwaroh (International Journal of Business, Law, and Education, 2026)
Purpose: This article examines the stages of library-material collection development implemented at the Universitas Pendidikan Nasional (Undiknas) Library in Denpasar, Bali. Design/methodology/approach: The study uses a descriptive qualitative single-case design. Data were obtained through direct observation, structured interviews with the head librarian, library staff, and students, and document analysis of collection records, development procedures, and institutional policy documents. The analysis was organized through data reduction, thematic coding, cross-source comparison, and interpretation using the collection development cycle proposed by Evans and Saponaro. Findings: Collection development at the Undiknas Library is implemented through six interrelated stages: user-needs analysis, policy orientation, selection, procurement, weeding, and evaluation. The library has built a hybrid collection consisting of printed books, theses, textbooks, magazines, e-books, and institutional digital repository materials. The findings show that collection decisions are strongly shaped by curriculum relevance, lecturer and student requests, donations, grants, and borrowing statistics. However, the study also identifies three areas requiring strengthening: the formulation of an internal written collection development policy, more sustainable acquisition funding, and more systematic evaluation of digital and print collections. Originality/value: The article contributes case-based evidence from an Indonesian private university library and demonstrates how international collection-management theory can be operationalized in a local institutional context.